Composing a care of the self : a critical history of writing assessment in secondary English education - Carlson, David Lee (SensePublishers, 2012)
What do Germ Theory, self-psychology, the entrepreneur and the Bertillion Card have in common? They comprise a part of the historical dispositif for the emergence of the writing portfolio. This riveting Foucaultian-inspired genealogy travels through the history of medicine, criminality, psychology, political economics to reveal the epistemologies and practices of power/knowledge of the contemporary portfolio. In so doing, it challenges previous held beliefs about the germination of the secondary school, prevailing views of the dawning of secondary English as a discipline.